Identifying cardiovascular neurocircuitry involved in the exercise pressor reflex in humans using functional neurosurgery. - Basnayake, S; Hyam, J; Pereira, E; Schweder, P; Brittain, J; Aziz, T; Green, A; Paterson, D (2011)
Groups III and IV afferents carry sensory information regarding the muscle exercise pressor reflex, although the central integrating circuits of the reflex in humans are still poorly defined. Emerging evidence reports that the periaqueductal gray (PAG) could be a major site for integrating the "central command" component that initiates the cardiovascular response to exercise, since this area is activated during exercise and direct stimulation of the dorsal PAG causes an increase in arterial blood pressure (ABP) in humans. Here we recorded local field potentials (LFPs) from various "deep" brain nuclei during exercise tasks designed to elicit the muscle pressor reflex. The patients studied had undergone neurosurgery for the treatment of movement or pain disorders, thus had electrodes implanted stereotactically either in the PAG, subthalamic nucleus, globus pallidus interna, thalamus, hypothalamus, or anterior cingulate cortex. Fast Fourier transform analysis was applied to the neurograms to identify the power of fundamental spectral frequencies. Our PAG patients showed significant increases in LFP power at frequencies from 4 to 8 Hz (P < 0.01), 8 to 12 Hz (P < 0.001), and 12 to 25 Hz (P < 0.001). These periods were associated with maintained elevated ABP during muscle occlusion following exercise. Further increases in exercise intensity resulted in corresponding increases in PAG activity and ABP. No significant changes were seen in the activity of other nuclei during occlusion. These electrophysiological data provide direct evidence for a role of the PAG in the integrating neurocircuitry of the exercise pressor reflex in humans.